Postpamięć czy pamięć indywidualna? Doświadczenie Zagłady zobrazowane w reportażu Agaty Tuszyńskiej pt. "Bagaż osobisty po marcu" - Chłosta-Zielonka, Joanna (Acta Neophilologica, 2020)
The aim of this article is to analyze the latest reportage by Agata Tuszyńska entitled Personal luggage. After March [2018]. The author deals with the shared experience of the generation of young Jews, the children of those who survived the Holocaust, living in the Polish People’s Republic. The category of post-memory, defined in 1997 by Marianne Hirsch, is assigned to this experience reported in the text. The interpretation of the protagonists’ statements, however, demonstrates that it does not work in their case. Their memories are of a genuine generational character, but they consist of a variety of individual memories, in which the Holocaust is on the margin of experience.